Halal Fashion Purchase Decision Model: Product Quality and Modern Digital Tekhnology - Nurul Jannah; Nurhayati; Zuhrinal M. Nawawi (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Indonesia has achieved first place in the global modest fashion sector with halal fashion consumption projected to reach USD 330.5 billion by 2025. However, there is a gap between the size of the market potential and consumer purchasing behavior, especially among urban Muslim millennials and Generation Z, who have unique characteristics and preferences in the digital era. This study aims to analyze the halal fashion purchase decision model by integrating product quality and modern digital technology factors among urban Muslim millennial and Generation Z consumers in Indonesia Method: This study uses a quantitative approach with an explanatory design through the Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) method. Data were collected from 300 urban Muslim millennial and Generation Z respondents using purposive sampling technique. The measurement instrument used a Likert scale questionnaire to measure product quality, modern digital technology, and halal fashion purchase decisions. Results: The results show that the structural model developed has strong predictive power with an R-Square value of 0.626, meaning that 62.6% of the variation in halal fashion purchase decisions can be explained by product quality and modern digital technology variables. Modern digital technology emerged as the dominant factor most significantly influencing halal fashion purchase decisions with a t-statistic value of 8.512 and p-value 0.000, categorized as having a strong influence with f-square value of 0.381. Meanwhile, product quality has a significant but relatively weak influence with t-statistic 3.246, p-value 0.001, and f-square value of 0.074. Conclusion: The findings indicate a paradigm shift in urban Muslim consumer priorities from traditional product quality orientation toward digital accessibility and experience. This research contributes theoretically to the development of consumer behavior theory in the context of Islamic economics by integrating Theory of Planned Behavior from an Islamic perspective and Maqashid Syariah theory.